Cross-Sectional and Longitudinal Associations Between Psychosocial Well-Being and Cardiometabolic Markers in European Children and Adolescents. Issue 8 (October 2020) - Thumann, Barbara F.; Börnhorst, Claudia; Ahrens, Wolfgang; Arvidsson, Louise; Gwozdz, Wencke; Iguacel, Isabel; Mårild, Staffan; Molnár, Dénes; Rach, Stefan; Russo, Paola; Tornaritis, Michael; Veidebaum, Toomas; et al.
ABSTRACT: Objective: Research examining aspects of positive mental health as potential predictors of cardiometabolic health in young populations is scarce. We investigated the associations between psychosocial well-being and waist circumference (WAIST), blood pressure (BP), the homeostasis model assessment for insulin resistance, triglycerides, and high-density lipoprotein cholesterol considering life-style factors as mediators. Methods: Data of European children and adolescents participating in the baseline (2007/2008), first follow-up (FU1; 2009/2010) and second follow-up (FU2; 2013/2014) examinations of the IDEFICS/I.Family study were used ( n cross-sectional = 6519; n longitudinal = 1393). A psychosocial well-being score was calculated from 16 items on emotional well-being, self-esteem, and social relationships (0–48 points). Cardiometabolic markers were transformed to age- and sex-specific and, in case of BP, also height-specific z scores. Life-style factors included diet, physical activity, sleep, and electronic media use. Applying path analysis, we obtained unstandardized estimates of direct and indirect effects of well-being on cardiometabolic markers. Results: Cross-sectionally, well-being score showed a negative direct and a negative indirect effect through life-style factors on WAIST z score (estimate per 4-point increase, −0.051 [ p = .001] and −0.014 [ p < .001], respectively). Longitudinally, positive changes in well-being score between baseline and FU1 and between FU1 and FU2, respectively, demonstrated negative indirect effects through life-style factorsFU2 on WAIST z scoreFU2 . Both cross-sectionally and longitudinally, higher levels of well-being showed lowering indirect effects on homeostasis model assessment, BP, and triglyceride z scores and an increasing indirect effect on high-density lipoprotein cholesterol z score through both life-style factors and WAIST z score. Conclusions: These results supported our hypothesis that a healthier life-style may be one mechanism through which higher well-being is linked with lower abdominal obesity and fewer other cardiometabolic disorders in young populations. Trial Registration: Pan-European IDEFICS/I.Family children cohort, ISRCTN registry number: ISRCTN62310987 (http://www.isrctn.com/ISRCTN62310987 ).